Corporate social responsibility in health sector: a case study in the government hospitals in Medan, Indonesia - Lubis, Arlina Nurbaity (Business: Theory and Practice, 2018)
Contemporary society demands that every organization operate with a sense of social responsibility. Many organizations now include corporate social responsibility (CSR) activities in their work programs. In the health sector, however, the role of CSR has not been studied as intensively as in private corporations because the services provided by the health sector are already valued as directly serving humanity. This research aims to evaluate the impact of CSR on the health sector, specifically on government hospitals. This model was developed by analyzing the influence of CSR on hospital reputation, customer loyalty, and hospital values. By answering questionnaires, a total of 200 hospital patients from four government hospitals participated in the study. The proposed model was evaluated using path analysis with AMOS tools. The results of this study provide empirical evidence that overall, CSR positively affects the reputation of the hospital, patient loyalty, and hospital value. Although there is a direct negative effect of CSR on hospital value, the larger influence of indirect effect that occurs through the mediating role of reputation and patient loyalty variables shows that CSR is able to increase the hospital value. Practically, these results imply that CSR should be applied as a strategic tool in improving the value of the hospital.